Regression Model Development For Two Layer Control System Based on Engine RPM - Sivarao, Subramonian; sivasan, karan nair (2008)
Speed sensing applications have been widely known in the automotive industry as, most of the gadgets require speed sensing system to control the desirable output. This experimental project is expected to be applied in the automotive field, especially in the mode of luxurious and speeding cars. One of the applications projected is to control the body lifting of a car. The vertical linear motion of a car body will be controlled by the car speed, which is also proportional to the engine speed. The car body will be lowered to balance to its center of gravity (C.G), hence stabilize the car when it is driven at high speed. Likewise, when the rpm of the engine decreases, the body of the car will tend to resume to normal position. With this system, there will be less diagonal pitching and constant ride height base on conditions. The regression model also developed in this work to bring the design to its near-net design more economically.